A comparative review: Physicochemical and antioxidant properties of stingless bee (Heterotrigona itama) honey and tualang (Apis dorsata) honey / Nurul Afiqah Mohammad Nadzree and Mohd Hilmi Hassan - Mohammad Nadzree, Nurul Afiqah; Hassan, Mohd Hilmi (2021)
Stingless bee honey and tualang honey are the most two common multi-floral honey available in Malaysia which is produced by Heterotrigona itama and Apis dorsata respectively. Currently, there is limited data on the comparative physicochemical and antioxidant properties of Malaysian honey. This review aims to evaluate and increase knowledge about the physicochemical composition and antioxidant activity of Malaysian honey produced by these two different species of bees. Parameters such as moisture content, pH, hydroxymethylfurfural (HMF), diastase activity, colour intensity, ash content, total phenolic content (TPC), FRAP and DPPH assays were analysed. Findings revealed that tualang honey showed higher pH, HMF reading and diastase number. Meanwhile kelulut honey is higher in moisture, ash content, total phenolic content and greater colour intensity. Besides, the antioxidant capacity was analysed to be higher in kelulut honey as it possessed lower DPPH values and greater FRAP values than tualang honey. Overall, both types of honey violate the Codex Alimentarius standard for honey in terms of moisture and diastase activity. The international standard for honey is unfavourable to the honey produced by these two types of bees. Apart from the different types of bees, the physicochemical properties of honey are diverse due to geographical origin, botanical source and seasonal factors. Further research is required to discover and understand the potential development of these honey into various food products.